Coltricia aridicola sp. nov. derived from the Coltricia perennis complex (Hymenochaetaceae) confirmed by molecular phylogeny - Wu, Ying-Da; Bian, Lu-Sen; Vlasák, Josef; Liu, Hong-Gao; Dai, Yu-Cheng (Phytotaxa, 2024)
A new polypore in the family Hymenochaetaceae, Coltricia aridicola, is described and illustrated from China and the USA based on morphology and phylogenetic analysis. The species was found in northeast and southwest China and western USA, growing on soil in gymnosperm forests. It is characterized by an annual growth habit, centrally stipitate basidiocarps with regular pilei, pileal surface distinctly zonate, medium-sized pores as 3–4 per mm, a monomitic hyphal system, generative hyphae with simple septa, the presence of antler-like hyphal elements at the pileal surface, contextual hyphae almost twice the diameter of the tramal hyphae, thick-walled, yellowish, cyanophilous, oblong-ellipsoid basidiospores measuring 7–7.8 × 4.5–4.8 µm, and growth in dry environments such as burnt soil or open areas of ground in gymnosperm forests. The phylogenetic analysis based on ITS sequences showed that samples of C. aridicola nested in Coltricia, forming a monophyletic lineage with strong support (100 % BS, 100 % BP, 1.00 BPP). The differences between C. aridicola and its similar and related species in the genus are discussed.